C# programming for absolute beginners : learn to think like a programmer and start writing code - Vystavěl, Radek (Apress, 2021)
Get started using the C# programming language. Based on the authors 15 years of experience teaching beginners, this book provides you with a step-by-step introduction to the principles of programming, or rather, how to think like a programmer. The task-solution approach will get you immersed, with minimum theory and maximum action. What You Will Learn Understand what programming is all about Write simple, but non-trivial, programs Become familiar with basic programming constructs such as statements, types, variables, conditions, and loops Think like a programmer and combine these programming constructs in new ways Get to know C# as a modern, mainstream programming language, and Visual Studio as one of the worlds most popular programming tools This book is for those with very little or no experience in computer programming, who know how to use a computer, install a program, and navigate the web. Radek Vystavel started programming at a young age and has been doing it ever since, as well as sharing it with others. Having worked as both a programming teacher in college and privately, as a programmer, Radek started writing books on programming because many of his students had no previous knowledge of programming and he had difficulty finding a suitable textbook for them. Throughout the years he has gained a unique insight into what resonates when teaching beginners.